Casebook on Insurgency and Revolutionary Warfare - Tompkins Jr, Paul J.; United States Army Special Operations Command (Public Intelligence, 2013)
This Casebook was originally published by the US Army Special Operations Research Office in December 1962. As we developed the Assessing Resistance and Insurgent Strategies (ARIS) project and work began on the new Casebook, we determined that the studies within this volume are still important and relevant and thus this first volume should be republished. This volume covers roughly the first half of the nineteenth century through 1962; Volume II covers 1962 through 2009. Each book addresses twenty-three insurgencies. The majority of the book was reproduced exactly as it appeared originally, with some minor spelling and punctuation corrections as well as changes in for- matting to allow for modern typesetting and to match the new sec- ond volume in presentation. In the original, some of the footnotes or endnotes have no corresponding reference in the text, and in some instances, a reference number exists but has no corresponding foot- note; these were left as is. This volume includes the following formats: a softbound book, a hardbound book, a PDF, and an EPUB. When citing this volume in scholarly work, please refer to the PDF version available at www.soc.mil.
Keywords: Rebeliones; Guerra